PELAKSANAAN PENDIDIKAN AGAMA KRISTEN GEREJA DAN KELUARGA UNTUK MEMBANGUN IMAN REMAJA GBI BATU AJI - Tony Suhartono (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
This research is based on advances in digital-based technology that cause teenagers to experience a decline in faith in God. Most churches are more busy looking for souls to continue to grow than they are with youth's faith growth. Families are preoccupied with earning a living for the sake of the economy rather than developing the faith of teenagers. In connection with the problems above, the writer formulates the problems as follows: First, whether and how to build the faith of today's Christian youth through the church and family. Second, what is being done in carrying out Christian Religious Education at the Indonesian Bethel Church in the Batu Aji area to build the faith of today's youth. Third, do the Christian families at the Indonesian Bethel Church in the Batu Aji area carry out Christian Religious Education in building the faith of youth. After the research data were collected, the authors processed and analyzed to find out how the implementation of Christian religious education in the church and how the implementation of Christian education in the family in building youth faith. To find answers, the authors adjust the field observation data with the literature review data discussed in chapter two, with a simple descriptive analysis, the authors try to find things that are important in the implementation of church and family Christian religious education to build faith for youth. After everything is analyzed, the author finally concludes that the implementation of Christian religious education for churches and families to build youth faith is not optima.